Tanjung Batu, Bebar the potential of Tanjung Batu, Pekan Pahang as an ecotourism destination - Rohiat, Mohd Akmal; Abdul Razzaq, Abdul Rasid; Hamzah, Amran; Mustafa, Mohamad Zaid; Hassan, Azman (Atlantis Press, 2017)
This research paper explores the Tanjung Batu's tourism resources to explore any activities and features to become a potential ecotourism destination. In order for the tourism destination like Tanjung Batu sub-district of Bebar as ecotourism destination; the main factor will be the tourism resources besides other services and facilities. Based on an understanding of this tourism resource inventory studies, the purpose of this paper is to provide an overall assessment of the resource features in terms of development opportunities and constraints to be a promoted as an ecotourism destination. Data collection and analysis were done through observations and interviews conducted with a selected group of rough the community differing in cultural practice and economic activities with the help of the following checklist - natural resources analysis, cultural resources analysis, community analysis, site analysis and tourism services and facilities analysis. After concluding the study, Tanjung Batu has within its own material and facilities subject to a little bit of enhancement to be a potential tourism destination and attraction that may offer local and foreign tourist a different level of experience that they never had before elsewhere.Keywords—component; formatting; style; styling; insert (key words)